The Role of Bukhara Jurists in the Development of the Hanafi School - Ochilovich, Nematov (Jurnal Pendidikan Non formal, 2024)
This article highlights the historical significance of the city of Bukhara and the role of Bukhara’s jurists in the development of the Hanafi school of thought founded by Abu Hanifa (may Allah have mercy on him). The article discusses the scholarly activities of Abu Hafs Ahmad ibn Hafs al-Kabir al-Bukhari, his students, and the madrasa traditions in Bukhara. In particular, the article provides a detailed account of the introduction and spread of the Hanafi school in Mavarounnahr, as well as the contributions of Abu Hafs Kabir to science and knowledge.